Approach to diagnosis and treatment to urologic emergencies - Alzahrani, Fahad Ahmed; Alhelali, Hatim Osama; Alismail, Khalid Itran; Alraddadi, Khaled Soud; Alghamdi, Mohammed Saeed; Alzhrani, Khalid Hassan; Alahmadi, Muhammad Abdulrahman; Alzahrani, Bader Abdullah; Alshehri, Saleh Ali; Basyouni, Nourhan Sulaiman; Almarzooq, Jawad Najeeb (International Journal Of Community Medicine And Public Health, 2023)
Acute urinary retention, which is an emergency presents a significant challenge, for healthcare providers especially among elderly men. This condition often leads to dysfunction and genital pain causing distress and anxiety for those affected. The likelihood of experiencing acute urinary retention increases with age, with men in their 70s facing a 10% risk that escalates to, over 30% in their 80s. Dealing with both dysfunction and acute pain adds complexity to the clinical management of these cases. This summary highlights the role played by emergency physicians in the management of this troubling urologic emergency. The initial approach involves conducting an evaluation that includes assessing medical history performing physical examinations and conducting relevant diagnostic tests. Promptly identifying the causes, which can range from prostatic hyperplasia and urethral strictures to infections or neurogenic conditions is crucial. Pain relief is an immediate concern, prompting the administration of analgesics to alleviate patient discomfort. Concurrently, urinary catheterization, skillfully performed by the emergency physician, effectively resolves the urinary obstruction, providing substantial relief. Referral to urologists ensures a comprehensive etiological assessment and the formulation of an individualized management plan. In summary, effectively managing retention, with associated erectile dysfunction and genital pain, requires a collaborative effort between emergency physicians and urological specialists. By identifying the cause, providing skilled pain management and expertly performing urinary catheterization emergency physicians play a crucial role in relieving patient discomfort.